The Marketing Power of TikTok: A Content Analysis in Higher Education - Deni Adha Akbari; Bella Jastacia; Edi Setiawan; Dwi Widya Ningsih (Bina Nusantara University, 2022)
Nowadays, social media is a common thing for every generation. Aside from entertainment and education, there are numerous business applications for this technology. By using social media, marketers can display their products in creative ways, such as creating videos. One of the most popular social media is TikTok. The research aimed to achieve more profound effects of TikTok for promoting higher education. The research applied a qualitative description by analyzing the content of a TikTok account (@uhamkapmb). Data were taken from the contents from August to October 2021. Then, the research calculated views, comments, likes, profile views, and video views of the contents and analyzed them. Supplementary, to evaluate @uhamkapmb’s TikTok account, the researchers shared surveys about customers’ satisfaction with the contents. The respondents were prospective and current students of UHAMKA with an age range of 18 to 25 years. Around 100 respondents were observed, and the data were processed using MS Excel. The result shows a significant increase in September (19.077,84) which is more than in August (6.941,42) and October (8.690,2) 2021. Moreover, the famous content of @uhamkapmb is re-registration. In addition, the customers agree that @uhamkapmb’s contents are already complete, precise, easy to reach, and interesting.